Implementasi Kewenangan Pemerintah Daerah Kabupaten Alor Dalam Upaya Perlindungan Mangrove Di Kecamatan Teluk Mutiara Berdasarkan Peraturan Bupati Alor Nomor 4 Tahun 2013 - Maara, Etvin Petrus; Asnawi, Norani; Tuan, Yohanes (Artemis Law Journal, 2025)
government authority in mangrove protection efforts in Teluk Mutiara District, Alor Regency is needed because of the surrounding community's destruction of mangroves. This study uses an empirical method. The data collection techniques used are through interviews and literature studies. The purpose of this study was to determine the implementation of the authority of the Alor Regency Government in mangrove protection efforts. In efforts to protect mangrove forests, it consists of the authority of guidance and supervision, first guidance, guidance is carried out by conducting socialization about mangrove forests to the surrounding community and also students around the mangrove, monitoring or evaluation, planting mangroves and also conducting conservation training for young men and women to provide an understanding of the importance of conservation. Second Supervision, Supervision carried out by the government is still carried out by forming a supervisory team called PPNS (Civil Investigator Employees) whose duties include monitoring and evaluation, the government also forms POKMASWAS to assist the Government in terms of supervision, the factors that influence the authority of the Alor Regency government in mangrove protection efforts consist of internal factors and external factors. Internal factors consist of ASN authority, budget and resources, while external factors consist of land, community resources and also lack of community empowerment.